Pembuatan Aplikasi Marketplace Untuk Mahasiswa dan Alumni Universitas Kristen Petra - Oen David Haryono; Kristo Radion Purba; Lily Puspa Dewi (Jurnal Infra, 2017)
Nowadays, similar marketplace applications have diverse features and good security system. But many of internet users abuse the marketplace facilities just for personal benefit fraud for example by using invalid personal data (fake account) thus lost buyer trust in transaction through the marketplace sites. Based on this need, a marketplace application for students and alumnus of Petra Christian University has been made as a source of information and an intermediary to connect between sellers and buyers, and also to build buyer trust against the seller by using a username that has been integrated with valid data.Marketplace application for students and alumnus of Petra Christian University is designed using the bootstrap framework, supported with AJAX, PHP and SOAP on the features of third-party transactions, PayPal, and also mediating complaints via live chat. This application has been integrated with email and password which are recorded in the student database of Petra Christian University (john.petra.ac.id). This application also equipped with HTTPS, Anti-XSS (Cross Site Scripting) and Anti SQL Injection as safety standards.As the results, this marketplace application can establish buyer trust against the seller for online transaction by using username that has been intergrated with valid data. This application has been equipped with third party transactions features and paypal. In addition, there is reviewuser features that help to convince buyers to choose definite seller. As well as a live chat feature to mediate complaints between buyers, sellers, and admin.